Literary Studies and Well-Being Structures of Experience in the Worldly Work of Literature and Healthcare - Schleifer, Ronald (Bloomsbury Academic, 2022)
Drawing on a broad range of disciplines, this book advances a sophisticated and compelling analysis of literary studies and the ways in which it shares its goals with the worldly concerns of the health and medical humanities, contributing to debates around the value of literary studies as a discipline and the humanities more broadly.